If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x + -2)(3x + 5) = 0 Reorder the terms: (-2 + x)(3x + 5) = 0 Reorder the terms: (-2 + x)(5 + 3x) = 0 Multiply (-2 + x) * (5 + 3x) (-2(5 + 3x) + x(5 + 3x)) = 0 ((5 * -2 + 3x * -2) + x(5 + 3x)) = 0 ((-10 + -6x) + x(5 + 3x)) = 0 (-10 + -6x + (5 * x + 3x * x)) = 0 (-10 + -6x + (5x + 3x2)) = 0 Combine like terms: -6x + 5x = -1x (-10 + -1x + 3x2) = 0 Solving -10 + -1x + 3x2 = 0 Solving for variable 'x'. Factor a trinomial. (-5 + -3x)(2 + -1x) = 0Subproblem 1
Set the factor '(-5 + -3x)' equal to zero and attempt to solve: Simplifying -5 + -3x = 0 Solving -5 + -3x = 0 Move all terms containing x to the left, all other terms to the right. Add '5' to each side of the equation. -5 + 5 + -3x = 0 + 5 Combine like terms: -5 + 5 = 0 0 + -3x = 0 + 5 -3x = 0 + 5 Combine like terms: 0 + 5 = 5 -3x = 5 Divide each side by '-3'. x = -1.666666667 Simplifying x = -1.666666667Subproblem 2
Set the factor '(2 + -1x)' equal to zero and attempt to solve: Simplifying 2 + -1x = 0 Solving 2 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + -1x = 0 + -2 Combine like terms: 2 + -2 = 0 0 + -1x = 0 + -2 -1x = 0 + -2 Combine like terms: 0 + -2 = -2 -1x = -2 Divide each side by '-1'. x = 2 Simplifying x = 2Solution
x = {-1.666666667, 2}
| -10/x=5/x-10/3 | | x-255=443 | | 46=3u-11 | | 600=2500(X)(4) | | (5x-2)/2x-18 | | 4n-6.4=2(n+1.3) | | (5x-2)/2x-18=0 | | x+255=433 | | 6x^2+7x-2= | | -4r+12=-72 | | 4/840=4/x | | 4/3x-2=16 | | 840/x=3/4 | | 3x-5(-2+3x)=10 | | r^2+69r-216=0 | | 2/7t-10/7t | | x-0.7=8.59 | | 0=-16t+vt+16 | | 11A-13=-7A^2 | | j^2-20j+36=0 | | 0=(x-9)(3x+1) | | 3/840=4/x | | n-3/4=5/12 | | 3m-2(m+7)=m-14 | | log(2x)+log(x)=11 | | n-3/4 | | (48w^9x^3/3w^5x^5)^1/2 | | -7(t+5)=14 | | 4/5x=2 | | -4x=-18+5x | | (5x^0/10x^-3y^2)^2 | | 12/x=5/9 |